Alternativa verde para análise de phyllanthus niruri por CLAE - Pelissari, João Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
In 2009, a list containing 71 medicinal species was published with the purpose of guiding studies on the development of herbal medicines, the so-called National List of Medicinal Plants of Interest of SUS (Renisus). Among these species is Phyllanthus niruri (stone breaker). Several studies of P. niruri report important pharmacological actions, as well as chemical studies that indicate the presence of several secondary metabolites. However, in these works High Performance Liquid Chromatography (HPLC) is the most used technique in which toxic solvents are used that can cause several damages to the health of the analyst and to the environment. In this context, this work presents the development of a chromatographic methodology, which allows the analysis of the profile of P. niruri by HPLC, using water and ethanol as a mobile phase (environmentally friendly solvents), carried out by a rational and numerical strategy of reduced experiments. With the application of a fractional factorial design, it was possible to determine the chromatographic parameters important for the separation of stone breaking metabolites by HPLC, which were: initial percentage of ethanol and temperature of analysis. After the identification of the main parameters, a Central Composite Design was carried out, which enabled the obtainment of a mathematical model that was able to calculate the ideal values of the analyzed parameters obtaining a green chromatographic profile with the highest number of peaks and with the best possible distribution addressing 6 principles from the 12 of green chemistry

Em 2009, foi divulgada uma lista contendo 71 espécies medicinais com o intuito de nortear estudos no desenvolvimento de fitoterápicos, a chamada Relação Nacional de Plantas Medicinais de Interesse do SUS (Renisus). Dentre essas espécies encontra-se a Phyllanthus niruri (quebra-pedra). Diversos estudos de P. niruri relatam importantes ações farmacológicas, bem como estudos químicos que indicam a presença de vários metabólitos secundários. Contudo, nesses trabalhos a cromatografia líquida de alta eficiência (CLAE) é a técnica mais utilizada na qual são utilizados solventes tóxicos que podem trazer vários danos a saúde do analista e ao meio ambiente. Diante deste contexto, este trabalho apresenta o desenvolvimento de uma metodologia cromatográfica, que permite a análise do perfil de P. niruri por CLAE, utilizando água e etanol como fase móvel (solventes ambientalmente amigáveis), realizado por uma estratégia racional e com número de experimentos reduzido. Com a aplicação de um planejamento fatorial fracionário foi possível determinar os parâmetros cromatográficos importantes para a separação dos metabólitos de quebra-pedra por CLAE que foram: porcentagem inicial de etanol e temperatura de análise. Após a identificação dos principais parâmetros foi realizado um Planejamento de Composto Central que possibilitou a obtenção de um modelo matemático que foi capaz de calcular os valores ideais dos parâmetros analisados obtendo um perfil cromatográfico verde com o maior número de picos e com a melhor distribuição possível abordando 6 princípios dos 12 de química verde
Keywords: Analise cromatografica; Quimiometria; Química verde; Cromatografia líquida de alta eficiência